Disentangling a Holobiont – Recent Advances and Perspectives in Nasonia Wasps - Dittmer, Jessica; van Opstal, Edward J.; Shropshire, J. Dylan; Bordenstein, Seth R.; Hurst, Gregory D. D.; Brucker, Robert M. (Frontiers in Microbiology, 2016)
The parasitoid wasp genus Nasonia (Hymenoptera: Chalcidoidea) is a well-established model organism for insect development, evolutionary genetics, speciation and symbiosis. The host-microbiota assemblage which constitutes the Nasonia holobiont (a host together with all its associated microbes) consists of viruses, two heritable bacterial symbionts and a bacterial community dominated in abundance by a few taxa in the gut. In the wild, all four Nasonia species are systematically infected with the obligate intracellular bacterium Wolbachia and can additionally be co-infected with Arsenophonus nasoniae. These two reproductive parasites have different transmission modes and host manipulations (cytoplasmic incompatibility vs. male-killing, respectively). Pioneering studies on Wolbachia in Nasonia demonstrated that closely-related Nasonia species harbor multiple and mutually incompatible Wolbachia strains, resulting in strong symbiont-mediated reproductive barriers that evolved early in the speciation process. Moreover, research on host-symbiont interactions and speciation has recently broadened from its historical focus on heritable symbionts to the entire microbial community. In this context, each Nasonia species hosts a distinguishable community of gut bacteria that experiences a temporal succession during host development and members of this bacterial community cause strong hybrid lethality during larval development. In this review, we present the Nasonia species complex as a model system to experimentally investigate questions regarding: (i) the impact of different microbes, including (but not limited to) heritable endosymbionts, on the extended phenotype of the holobiont, (ii) the establishment and regulation of a species-specific microbiota, (iii) the role of the microbiota in speciation, and (iv) the resilience and adaptability of the microbiota in wild populations subjected to different environmental pressures. We discuss the potential for easy microbiota manipulations in Nasonia as a promising experimental approach to address these fundamental aspects.